2003
DOI: 10.1038/sj.cdd.4401321
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila wing differentiation factor Vestigial–Scalloped is required for cell proliferation and cell survival at the dorso-ventral boundary of the wing imaginal disc

Abstract: Links between genes involved in development, proliferation and apoptosis have been difficult to establish. In the Drosophila wing disc, the vestigial (vg) and the scalloped (sd) gene products dimerize to form a functional transcription factor. Ectopic expression of vg in other imaginal discs induces outgrowth and wing tissue specification. We investigated the role of the VG-SD dimer in proliferation and showed that vg antagonizes the effect of dacapo, the cyclin-cdk inhibitor. Moreover, ectopic vg drives cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 55 publications
4
45
0
Order By: Relevance
“…(18) or sd (25) expression grow poorly (3-5 cells) and disappear from the wing blade 24 h after clone initiation (data not shown). This finding indicates that vg expression is formally required for the survival of wing blade cells (1,20). The cell survival and growth of mutant cells for vg were not favored in a Minute (M) genetic background either, dying quickly as it happens in a WT background (data not shown).…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…(18) or sd (25) expression grow poorly (3-5 cells) and disappear from the wing blade 24 h after clone initiation (data not shown). This finding indicates that vg expression is formally required for the survival of wing blade cells (1,20). The cell survival and growth of mutant cells for vg were not favored in a Minute (M) genetic background either, dying quickly as it happens in a WT background (data not shown).…”
Section: Resultsmentioning
confidence: 76%
“…vg is symmetrically expressed from early larval development in both sides of D͞V boundary, integrating inputs from the A͞P (dpp signaling) and D͞V (wg and N signaling) axes of growth (17)(18)(19). Recent reports (1,20) have shown that the lack of function of the Vg-Sd complex prevents the development of the wing blade, affecting cell survival in distal wing territories. Unlike the lack of function of the Vg-Sd complex, the overexpression in vivo (1,14,18,(21)(22)(23) or in cell culture (1) can promote cell proliferation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that TEAD may have a role in YAP function. Interestingly, Scalloped, the Drosophila TEAD homolog, plays some roles in regulating cell proliferation and apoptosis (Delanoue et al 2004), suggesting an intriguing possibility of Scalloped as a Yki target transcription factor. The bantam microRNA plays a critical role in Drosophila to mediate the Hippo pathway signaling, but there is no obvious bantam homolog in human genome ; Thompson and Cohen 2006).…”
Section: Yap In Tumorigenesismentioning
confidence: 99%